2017
DOI: 10.1038/s41598-017-07946-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in energy expenditure, body temperature and activity patterns in llamas (Lama glama)

Abstract: Mammals typically keep their body temperature (Tb) within a narrow limit with changing environmental conditions. There are indications that some wild ungulates can exhibit certain forms of energy saving mechanisms when ambient temperatures are low and/or food is scarce. Therefore, the aim of the study was to determine if the llama, one of the most extensively kept domestic livestock species, exhibits seasonal adjustment mechanisms in terms of energy expenditure, Tb and locomotion. For that purpose llamas (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 78 publications
(99 reference statements)
2
17
1
Order By: Relevance
“…Body temperature and metabolic rate generally correlates well across vertebrate species 24 and within individuals 25,26 (but not always 27 ), and hypothermia may thus be indicative of hypometabolism. Both hypothermia and hypometabolism have previously been reported for a variety of mammal species 1,3 , including high latitude ungulates 5 , as adaptations to the annual cycle in seasonal environments. However, and more importantly, we revealed a link between T b , activity level, and pregnancy status in muskoxen.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Body temperature and metabolic rate generally correlates well across vertebrate species 24 and within individuals 25,26 (but not always 27 ), and hypothermia may thus be indicative of hypometabolism. Both hypothermia and hypometabolism have previously been reported for a variety of mammal species 1,3 , including high latitude ungulates 5 , as adaptations to the annual cycle in seasonal environments. However, and more importantly, we revealed a link between T b , activity level, and pregnancy status in muskoxen.…”
Section: Discussionmentioning
confidence: 87%
“…In mammals, behavioural adaptations may involve seasonal changes in locomotor activity and basking 1 . Physiological adaptations include lowered metabolic rate and lowered body temperatures to conserve energy in response to adverse environmental conditions, ranging from daily torpor to true hibernation 2 , and a variety of such energy conserving strategies has been observed across a variety of species, including ungulates 1,[3][4][5] . Such energy-conserving strategies may, however, depend on intrinsic condition and/or reproductive status of the individual.…”
mentioning
confidence: 99%
“…Thus, energy reserves not only provide a source of energy during food scarce periods, but are also likely an integral part of the mechanism driving individual variability in heterothermy. Daily activity level can also substantially affect energy expenditure, and animals might change their activity level according to exogenous (e.g., food level, environmental conditions) or endogenous (e.g., energy reserves, hormones) cues (Arnold et al., 2006; Riek et al., 2017). Schmidt et al.…”
Section: Discussionmentioning
confidence: 99%
“…For endothermic species that do not migrate over vast distances, behavioral and physiological adaptations are the only available strategies to minimize exposure to local conditions and to mitigate the impacts of energy limitation (Signer et al., 2011). Species can reduce their energy expenditure by adjusting locomotor activity, body size, body temperature, and metabolic rates (Arnold et al., 2006; Brinkmann et al., 2012; Dehnel, 1949; Riek et al., 2017). Reduced body temperature ( T b ) and metabolic rate associated with heterothermy and hypometabolism can range from long‐term hibernation to daily torpor (Geiser, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile striated caracaras on Saunders Island remain as active in winter as they are in summer, though they compress their activity into winter's shorter daylight hours. These results suggest that during winter, juvenile caracaras on Saunders do not employ the energy-saving strategies that some species exhibit when faced with seasonal food scarcity [44][45][46][47]. Moreover, we found that male caracaras are more active than females in both seasons, a possible behavioral expression of the reverse sexual size dimorphism common in the Falconidae family [48,49].…”
Section: Discussionmentioning
confidence: 87%